Willingness to Pay for Cause-Related Marketing: The Impact of Donation Amount and Moderating Effects - Koschate-Fischer, Nicole; Stefan, Isabel V.; Hoyer, Wayne D. (Journal of Marketing Research, 2012)
Companies increasingly employ cause-related marketing to enhance customer goodwill and improve their image. However, because these efforts have major implications for pricing strategy and firm profitability, understanding the relationship between the company's donation amount and customers’ willingness to pay is important. In particular, little is known about the moderating effects that influence this relationship or their underlying mechanisms. Study 1 confirms that two types of customer predispositions moderate the link between donation amount and willingness to pay: donation-related and cause-related predispositions. Three additional studies focus on the negative moderating effect of company–cause fit and provide insights into the underlying moderation process. Specifically, the motives customers attribute to the company mediate the moderating impact of fit on the donation amount–WTP link (Study 2), which occurs particularly in cases of utilitarian (Study 3) and privately consumed products (Study 4).